2008
DOI: 10.1513/pats.200804-039qc
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control in Longitudinal Studies with Computed Tomographic Densitometry of the Lungs

Abstract: To guarantee the reliability of densitometric data in clinical trials on pulmonary emphysema a quality control procedure is presented, to prevent that a measured progression in lung density could be reflected by a gradual change in the maintenance of the computed tomographic scanner. For that purpose, a foam phantom has been developed, which mimicks the densities of emphysematous lung tissue, fixed in a sealed Perspex box. Analysis software was developed to automatically compare the density readings with a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Because these scanner systems are regularly calibrated, we expect that this variation is smaller than the variation due to using different software-analysis packages. 25 However, this was not investigated in this study. Such a comparison would require additional CT scanning of patients with stroke and is, therefore, unethical because of an increase of radiation and contrast material and a delayed treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Because these scanner systems are regularly calibrated, we expect that this variation is smaller than the variation due to using different software-analysis packages. 25 However, this was not investigated in this study. Such a comparison would require additional CT scanning of patients with stroke and is, therefore, unethical because of an increase of radiation and contrast material and a delayed treatment.…”
Section: Discussionmentioning
confidence: 86%
“…In the absence of established international guidelines to guarantee the reliability of CT densitometry data in this study, a quality assurance procedure based on the current experience within this field was implemented [Stoel et al 2008]. The results showed that CT is a reliable endpoint for disease progression with higher sensitivity than conventional or other functional and symptomatic measures [Bakker et al 2005].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, lung density was adjusted for volume to determine lung density progression independently, thereby estimating any treatment effect on tissue loss alone. The theory and methodology are described in detail elsewhere [Stoel et al 2008]. In brief, the algorithm for the volume adjustment assumes that, for a given individual, there is a unique linear relationship between lung density and volume at each visit.…”
Section: Study Endpointsmentioning
confidence: 99%
“…The detection of GGNs and emphysema are important and challenging tasks, however, the next step after detection is to provide quantitative metrics that can be used to evaluate and assess disease progression; this task is complicated by the HU variability between systems. In certain diseases, even a 1 HU change may be clinically significant to demonstrate disease progression, as with alpha1-antitrypsin deficiency (Stoel et al 2008). Thus efforts at improved accuracy for lung density ascertainment is necessary to provide quantitative biomarkers for the further development of treatments for diseases such as emphysema and idiopathic pulmonary fibrosis (IPF) that are currently characterized by HU changes.…”
Section: Discussionmentioning
confidence: 99%